Marshall B. Coyne autograph collection - Coyne, Marshall B.
Autograph collection consisting of the autographs of President James Madison and his administration including cabinet members Albert Gallatin, Elbridge Gerry, and James Monroe.
Collector.
Collection material in English.
Keywords: Gallatin, Albert, -- 1761-1849.; Gerry, Elbridge, -- 1744-1814.; Madison, James, -- 1751-1836.; Monroe, James, -- 1758-1831.; Collectors